A robust new full control strategy without FOANR based on substitution method against nonlinear DFIG model for wind application - Boughazi Othmane; Bouiri Abdesselam; Benoudjafer Cherif (International Journal of Power Electronics and Drive Systems (IJPEDS), 2022)
In order to control the output power of wind application (WA) based on doubly fed induction generator (DFIG). The simple control (SC) strategy based on approaches via flux orientation and neglecting resistance (FOANR) to decoupled axes is the most common used in many previous studies, However this strategy FOANR present a linear synthesis, mainly to control DFIG simple model sensitive to internal and external disturbances, This research paper contribute to developed a robust new full control (FC) strategy based on substitution method (SM) to solving nonlinear coupled axes without FOANR to control nonlinear DFIG model, we use a proportional-integral (PI) controller by the most efficient method: indirect with double loop on each axis to control powers generated by DFIG and stator current directly, we check its performance and efficient compared to the same controller based on flux FOANR against DFIG nonlinear model.